STUDI KOMPERATIF ORIENTASI KEWIRAUSAHAAN, LINGKUNGAN KEWIRAUSAHAAN, DAN MINAT BERWIRAUSAHA SISWA SMK BUDHI DHARMA DENGAN SMK 1 NEGERI MOJOANYAR MOJOKERTO - Putri, Aqila Azzahra (Research Journal of Social Science and Economics, 2025)
Currently students lack interest in starting their own business, which can result in high unemployment rates in Indonesia. In such a situation, it is the responsibility of educators in Indonesia to attract students’ interest in entrepreneurship. The unemployment rate can be reduced by creating new jobs if students have an interest in entrepreneurship. This study was conducted to see if there are differences between SMK Budhi Dharma and SMK 1 Negeri Mojoanyar in terms of entrepreneurial orientation, entrepreneurial environment, and entrepreneurial interest. The type of research that the authors conducted included comparative research and also quantitative research. In this study, probality sampling was used as the sampling method. It is a random sampling method that uses samples from the population by using random sampling techniques. Students from the year 2021 at SMK Budhi Dharma with SMK 1 Negeri Mojoanyar became the sample for this study. 81 students for the total sample. T-test analysis and homogeneity test were used in this study. The t-test is used to determine whether or not there is a mean difference between two paired sample groups, while the homogeneity test is used to determine the similarity or inequality of variants.